Quality of Herbal Tea Combination Between Corn Silk and Stevia Leaf on Variation of Temperature and Drying Duration - Nafiza, Feny; Suryani, Titik (Universitas Muhammadiyah Surakarta, 2023)
Herbal tea combination between corn silk and stevia leaf is a functional drink for health and refreshment. Corn silk contains antioxidant compounds or flavonoids that lower blood glucose levels. Stevia leaf as a natural sweetener contain stevioside, rebaudioside A, rebadioside C, and dulcoside A which are 200 to 300 times sweeter than sucrose. The aim of this study was to know the levels of glucose, antioxidant activity, and organoleptic quality of herbal tea combination between corn silk and stevia leaf with variations of temperature and drying duration. The study used experimental methods and a complete random design (crd) of two factors, factor I drying temperature 45 °C and 50 °C, factor II drying duration 2 hours and 4 hours. The results of the study showed the highest glucose of herbal tea combination between corn silk and stevia leaf on S2L2 (drying temperature 50 °C and drying duration 4 hours) is 7,212 g/100 g. The optimum antioxidant activity and best organoleptic quality of herbal tea on S1L1 (drying temperature 45 °C and drying duration 2 hours) was 83,696 % and yellow color, sweet taste, herbal tea characteristic scent, and respectively.